Association between SARS-CoV-2 and exposure risks in health care workers and university employees – a cross-sectional study. Issue 6 (3rd June 2021) - Nygren, David; Norén, Jonas; De Marinis, Yang; Holmberg, Anna; Fraenkel, Carl-Johan; Rasmussen, Magnus
Abstract: Background: In health care workers SARS-CoV-2 has been shown to be an occupational health risk, often associated with transmission between health care workers. Yet, insufficient information on transmission dynamics has been presented to elucidate the precise risk factors for contracting SARS-CoV-2 in this group. Methods: In this cross-sectional study, we investigated association between questionnaire answers on potential exposure situations and SARS-CoV-2-positivity. Health care workers with and without COVID-19-patient contact at nine units at Skåne University Hospitals in Malmö and Lund, Sweden and university employees from Lund University, Sweden were enrolled. To limit impact of health care worker to health care worker transmission, units with known outbreaks were excluded. A SARS-CoV-2-positive case was defined by a previous positive PCR or anti-SARS-CoV-2 IgG in the ZetaGene COVID-19 Antibody Test . Results: SARS-CoV-2-positivity was detected in 11/51 (22%) health care workers in COVID-19-units, 10/220 (5%) in non-COVID-19-units and 11/192 (6%) University employees ( p  = .001, Fischer's exact). In health care workers, SARS-CoV-2-positivity was associated with work in a designated COVID-19-unit (OR 5.7 (95CI 2.1–16)) and caring for COVID-19-patients during the majority of shifts (OR 5.4 (95CI 2.0–15)). In all participants, SARS-CoV-2-positivity was associated with a confirmed COVID-19 case (OR 10 (95CI 2.0–45)) in the household. Conclusion: Our study confirmed previous findings of elevated risk of acquiring SARS-CoV-2 in health care workers in COVID-19-units, despite exclusion of units with known outbreaks. Interestingly, health care workers in non-COVID-19-units had similar risk as University employees. Further measures to improve the safety of health care workers might be needed. KEY POINTS: Previous findings of elevated risk of contracting SARS-CoV-2 in health care workers with COVID-19 patient contact was confirmed, despite exclusion of wards with known SARS-CoV-2 outbreaks. Further measures to improve the safety of health care workers might be needed.